2016
DOI: 10.1007/s10802-016-0145-9
|View full text |Cite
|
Sign up to set email alerts
|

Does the Environment Have an Enduring Effect on ADHD? A Longitudinal Study of Monozygotic Twin Differences in Children

Abstract: Environmental factors play a key role in the development of Attention-Deficit/Hyperactivity Disorder (ADHD), but the long-term effects of these factors are still unclear. This study analyses data from 1024 monozygotic (identical) twins in Australia, the United States, and Scandinavia who were assessed for ADHD in Preschool, Kindergarten, Grade 1, and Grade 2. Differences within each twin pair were used as a direct measure of non-shared environmental effects. The Trait-State-Occasion (TSO) model developed by Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…Unique environment factors contributed substantially to individual differences in ) and to a lesser extent in HI (.22-.50), more so than in previous studies. There are two predominant patterns of environmental influences on ADHD: transient effects contributing to single measurement occasions and stable effects that persist over time (Livingstone et al, 2016). As in previous studies, we found mostly transient unique environment factors (Chang et al, 2013;Faraone et al, 2015;Greven et al, 2011;Kuntsi et al, 2005;Larsson et al, 2004Larsson et al, , 2014Pingault et al, 2015).…”
Section: Environmental Contributions To the Longitudinal Architecture...supporting
confidence: 80%
“…Unique environment factors contributed substantially to individual differences in ) and to a lesser extent in HI (.22-.50), more so than in previous studies. There are two predominant patterns of environmental influences on ADHD: transient effects contributing to single measurement occasions and stable effects that persist over time (Livingstone et al, 2016). As in previous studies, we found mostly transient unique environment factors (Chang et al, 2013;Faraone et al, 2015;Greven et al, 2011;Kuntsi et al, 2005;Larsson et al, 2004Larsson et al, , 2014Pingault et al, 2015).…”
Section: Environmental Contributions To the Longitudinal Architecture...supporting
confidence: 80%
“…These might also include stable environmental factors (Conway et al, 2016; Kendler et al, 2011). An interesting find was that twin studies of depression have partitioned the variance of depression into that which is because of shared genetics and that which is because of shared environmental factors (Ask, Waaktaar, Seglem, & Torgersen, 2016; Eley & Stevenson, 1999; MuthĂ©n & MuthĂ©n, 1998–2010; Matthews et al, 2016; Rice, Harold, & Thapar, 2002; Tackett Waldman, Van Hulle, & Lahey, 2011; Zheng, Rijsdijk, Pingault, McMahon, & Unger, 2016; see also Livingstone et al, 2016). Both sets of estimates vary substantially (partially as a function of age or developmental level), with estimates of genetic contributions ranging from 2 to 57% (median = 21.5%) and estimates of shared environmental effects ranging from 1 to 38% (median = 36.5%); however, their combined effects are quite reliable (with a median of 52.5% and a range of 39% to 62%).…”
Section: Discussionmentioning
confidence: 99%
“…This result is notable in light of the rarity of nonshared‐environmental stability over time (e.g. Burt, Klahr, & Klump, ; Turkheimer & Waldron, ; although see Livingstone et al., ). The link between early‐childhood anxiety and peer problems and later educational achievement was explained by shared‐environmental factors.…”
Section: Discussionmentioning
confidence: 85%